Evaluation of growth performance and water quality of vannamei shrimp (Litopenaeus vannamei) in intensive cultivation systems - Mochamad Rio Rifalda Rifalda; Robin; Novita MZ (Universitas Djuanda, 2023)
The success of shrimp cultivation is assessed based on the resulting performance, survival, growth, and total shrimp production. Apart from parent quality and feed quality, water quality is a determining factor in the success of shrimp cultivation. Good water quality will increase cultivation productivity. The research aims to measure the performance of vannamei shrimp using an intensive cultivation system at PT Bumi Cimandala Lestari by paying attention to the quality of cultivation waters. This research uses a descriptive method by following the entire series of cultivation production in the Bumi Cimandala Lestari shrimp pond. The activity lasts three months, from August to November 2022 at PT. Bumi Cimandala Lestari is located at Kp. Cipeundeuy, Surade Village, Sukabumi Regency. The results showed that the average survival rate from 8 cultivation ponds reached 67% with a growth rate of 0.26 g/day. The total production obtained was 55.42 tons with a size of 70-100 fish/kg. Water quality during the study was within the optimal range. The pH value of the water ranges from 7-9 with salinity ranging from 18.1 – 20.4 ppt. Dissolved oxygen value > 5 mg/L, and alkalinity ranges from 122 – 183 mg/L. The research showed that cultivation ponds had a temperature range between 24.8-30.4 and DO ranging from 2.49-8.23 mg/L. Water quality conditions are thought to support the growth and survival of shrimp well